Effects of passive integrated transponder tags on short‐term feeding patterns in European perch (Perca fluviatilis). Issue 6 (8th September 2021) - Chrysafi, Anna; Jepsen, Niels; del Villar‐Guerra, Diego; Larsen, Martin H.; Skov, Christian
Abstract: We tested the feeding behaviour of small European perch ( Perca fluviatilis ) in a laboratory study during the first 24 h after handling and 23 mm passive integrated transponder (PIT) tag implantation. Feeding commenced almost immediately following tagging and overall feeding patterns were unaffected by tagging. However, untagged perch had more feeding events than PIT‐tagged individuals. This discrepancy could be attributed to post‐tagging effects or/and reduced room for food due to the presence of the tag in the body cavity.